The novel benzimidazole derivative BRP‐7 inhibits leukotriene biosynthesis in vitro and in vivo by targeting 5‐lipoxygenase‐activating protein (FLAP). (June 2014) - Pergola, C; Gerstmeier, J; Mönch, B; Çalışkan, B; Luderer, S; Weinigel, C; Barz, D; Maczewsky, J; Pace, S; Rossi, A; Sautebin, L; Banoglu, E; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose Leukotrienes (LTs) are inflammatory mediators produced via the 5‐lipoxygenase (5‐LOX) pathway and are linked to diverse disorders, including asthma, allergic rhinitis and cardiovascular diseases. We recently identified the benzimidazole derivative BRP‐7 as chemotype for anti‐LT agents by virtual screening targeting 5‐LOX‐activating protein (FLAP). Here, we aimed to reveal the in vitro and in vivo pharmacology of BRP‐7 as an inhibitor of LT biosynthesis. Experimental Approach We analysed LT formation and performed mechanistic studies in human neutrophils and monocytes, in human whole blood (HWB) and in cell‐free assays. The effectiveness of BRP‐7 in vivo was evaluated in rat carrageenan‐induced pleurisy and mouse zymosan‐induced peritonitis. Key Results BRP‐7 potently suppressed LT formation in neutrophils and monocytes and this was accompanied by impaired 5‐LOX co‐localization with FLAP. Neither the cellular viability nor the activity of 5‐LOX in cell‐free assays was affected by BRP‐7, indicating that a functional FLAP is needed for BRP‐7 to inhibit LTs, and FLAP bound to BRP‐7 linked to a solid matrix. Compared with the FLAP inhibitor MK‐886, BRP‐7 did not significantly inhibit COX‐1 or microsomal prostaglandin E2 synthase‐1, implying the selectivity of BRP‐7 for FLAP. Finally, BRP‐7 was effective in HWB and impaired inflammation in vivo, in rat pleurisy and mouse peritonitis, along with reducing LT levels. Conclusions and Implications BRP‐7 potently suppresses LT biosynthesis by interacting with FLAP and exhibits anti‐inflammatory effectiveness in vivo, with promising potential for further development.